Effect of cimetidine and sodium bicarbonate on pancreatic replacement therapy in cystic fibrosis. Issue 9 (September 1980) - Durie, P R; Bell, L; Linton, W; Corey, M L; Forstner, G G
Abstract : Fifteen patients with cystic fibrosis and pancreatic insufficiency were studied during four randomised seven day treatment periods in which they received only pancreatic supplement (Pancrelipase, 27 capsules per day) or supplement plus cimetidine (20 mg/kg body weight/24 h) or sodium bicarbonate (15 g/m2/24 h) alone or in combination. Dietary intake was not fixed but was restricted to foods of known fat and nitrogen content from which daily intakes could be computed. Faecal fat and nitrogen were calculated as g/24 h and percentage of intake. Addition of either cimetidine or bicarbonate resulted in significant improvement in fat and nitrogen excretion, which was not greater with the combination of both drugs. Cimetidine and sodium bicarbonate in these doses are therefore sufficient to produce maximal improvement in digestive activity of pancreatic supplements. Fat excretion per gram of intake fell with cimetidine and bicarbonate from 12 times the normal level, to normal, in patients consuming less than 120 g fat daily. Above this intake the dose of pancreatic supplement appeared to be inadequate. Faecal nitrogen excretion increased with nitrogen intake in all four periods, but, in contrast with fat excretion, the response to cimetidine and bicarbonate was not affected by the level of intake. Dietary intake appears to be a significant factor in determining the faecal output of fat and nitrogen in patients with pancreatic insufficiency and should be considered when determining the optimum amount of pancreatic supplementation.